#### Answer

LCD=(x-1)(x+1)(2x+1)(3x+1)

#### Work Step by Step

$\frac{2x}{3x^{2}+4x+1}$, $\frac{7}{2x^{2}-x-1}$
3$x^{2}$+4x+1=3$x^{2}$+x+3x+1=x(3x+1)+1(3x+1)=(x+1)(3x+1)
2$x^{2}$-x-1=2$x^{2}$+x-2x-1=x(2x+1)-1(2x+1)=(x-1)(2x+1)
LCD=(x-1)(x+1)(2x+1)(3x+1)

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

LCD=(x-1)(x+1)(2x+1)(3x+1)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.